3D printed self-adhesive PEGDA–PAA hydrogels as modular components for soft actuators and microfluidics. Issue 16 (27th March 2019) - Valentin, Thomas M.; DuBois, Eric M.; Machnicki, Catherine E.; Bhaskar, Dhananjay; Cui, Francis R.; Wong, Ian Y.
Abstract : Hydrogel building blocks that are stimuli-responsive and self-adhesive could be utilized as a simple "do-it-yourself" construction set for soft machines and microfluidic devices. Abstract : Hydrogel building blocks that are stimuli-responsive and self-adhesive could be utilized as a simple "do-it-yourself" construction set for soft machines and microfluidic devices. However, conventional covalently-crosslinked hydrogels are unsuitable since they are as static materials with poor interfacial adhesion. In this article, we demonstrate ion-responsive interchangeable parts based on composite hydrogels that incorporate both covalent and ionic crosslinking. We use light-directed 3D printing to covalently-crosslink poly(ethylene glycol) diacrylate in the presence of anionic poly(acrylic acid) of much higher molecular weight. The addition of trivalent cations acts to crosslink the anionic polymer chains together. Using high cation concentrations drives strong crosslinking, which can result in dramatic hydrogel contraction. Mismatched contraction of layered ion-responsive and non-ion-responsive hydrogels can control bending and twisting actuation, which is utilized for a gripping device. Alternatively, moderate cation concentrations permit strong self-adhesion between hydrogel surfaces. LEGO-like hydrogel blocks with internal channels and external mechanical connectors can be stacked into complex microfluidic device geometries including serpentine micromixers and multilevel architectures. This approach enables "plug-and-play" hydrogel parts for ionic soft machines that mimic actuation, sensing, and fluid transport in living systems.